Methylated actinomycin D, a novel actinomycin D analog induces apoptosis in HepG2 cells through Fas‐ and mitochondria‐mediated pathways. Issue 12 (20th July 2012) - Chen, Yongqiang; Liu, Jinjuan; Yuan, Bo; Cao, Chengliang; Qin, Sheng; Cao, Xiaoying; Bian, Guangkai; Wang, Zhe; Jiang, Jihong
Abstract Actinomycin D (Act D), a well known of clinical antitumor drug, has been used for the treatment of some highly malignant tumors, however, the clinical application was limited by its extreme cytotoxicity. In the present study, we reported that methylated actinomycin D (mAct D), a novel actinomycin D analog isolated from Streptomyces sp. KLBMP 2541 in our previous study, could not only exert stronger inhibitory effects on several human cancer cells than Act D in dose‐ and time‐dependent manner at ng concentrations, especially on HepG2 cells, but also lower cytotoxicity in normal cells (HL‐7702). Base on these results, HepG2 cells were treated for further study to illustrate the potential mechanism of mAct D. The results of nuclei morphology examination, DNA fragmentation detection, sub‐G1 analysis, annexin V‐FITC/PI staining and activation of caspase‐3 indicated mAct D significantly induced HepG2 cells apoptosis. Semiquantitative RT‐PCR and Western blot analysis revealed that mAct D induced apoptosis in HepG2 cells through mitochondria‐dependent pathway by increasing levels of caspase‐9, Bax, Bak while decreasing levels of Bcl‐2, Bid, and Fas‐dependent pathway by increasing levels of Fas, FasL, FADD, and caspase‐8. Subsequently, pretreatment with specific inhibitor of caspase‐8 Z‐LEHD‐FMK and caspase‐9 Z‐LEHD‐FMK significantly attenuated caspase‐3 activity, the cleavage of caspase‐3 and PARP, meanwhile increased the cell viability. In addition, p53 and mitochondrial transcription factor A (mtTFA) were also upregulated. Taken together, ng concentrations mAct D induces the apoptosis of HepG2 through Fas‐ and mitochondria‐mediated pathway and presents a potential novel alternative agent for the treatment of human hepatic carcinoma. © 2012 Wiley Periodicals, Inc.